2019
DOI: 10.1007/s11126-019-09628-1
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and Desire Thinking as Predictors of Problematic Facebook Use

Abstract: Emotion regulation and desire thinking in problematic Facebook use Funding sources: No external funding source for this study has been received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 24 publications
4
20
0
4
Order By: Relevance
“…However, in some cases, this may represent a maladaptive strategy that might foster a dysfunctional feedback loop reinforcing lonely individuals' anxiety in the specific pandemic circumstance. Accordingly, problematic social media use has already been evidenced as a dysfunctional emotional-regulation strategy (117)(118)(119), although it is frequently used to control mood (120)(121)(122)(123)(124). Thus, despite this excessive social media use denoting individuals' efforts to face their sense of loneliness and isolation, it might also foster more negative outcomes if forced by the situation and prolonged in time.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases, this may represent a maladaptive strategy that might foster a dysfunctional feedback loop reinforcing lonely individuals' anxiety in the specific pandemic circumstance. Accordingly, problematic social media use has already been evidenced as a dysfunctional emotional-regulation strategy (117)(118)(119), although it is frequently used to control mood (120)(121)(122)(123)(124). Thus, despite this excessive social media use denoting individuals' efforts to face their sense of loneliness and isolation, it might also foster more negative outcomes if forced by the situation and prolonged in time.…”
Section: Discussionmentioning
confidence: 99%
“…Research undertaken across numerous studies has shown that desire thinking is a transdiagnostic process as it is present across a range of targets, including alcohol (Caselli, Ferla, Mezzaluna, Rovetto, & Spada, 2012;Caselli, Gemelli, & Spada, 2017;Caselli & Spada, 2010), nicotine (Caselli, Nik cevi c, Fiore, Mezzaluna, & Spada, 2012;Caselli & Spada, 2010), food (Spada, Caselli, Fernie et al, 2015), gambling (Caselli & Spada, 2010;Fernie et al, 2014), problematic Internet (Spada, Caselli, Slaifer, Nik cevi c, & Sassaroli, 2014) social media use (Marino et al, 2019), and pornography (Allen, Kannis-Dymand, & Katsikitis, 2017; for a recent systematic review and meta-analysis see; Mansueto et al, 2019).…”
Section: Desire Thinkingmentioning
confidence: 99%
“…The diversity of contents related to physical appearance in a social network makes it easier for negative emotional responses to appear which not all users know how to manage with adaptive emotion regulation strategies (ER). Hormes, Kearns, and Timko (2014) and Marino et al (2019) found a positive relationship between problematic Facebook use and greater ER difficulties (experiential avoidance, emotional rejection, poor impulse control). Therefore, the use of a social network like Instagram could impede identifying, understanding and accepting emotional experiences derived from a setting which values and evaluates appearance.…”
mentioning
confidence: 94%